A Rigid Nanoplatform for Precise and Responsive Treatment of Intracellular Multidrug-Resistant Bacteria. (August 2022) - Qu, Shaoqi; Huang, Xiaoyong; Song, Xiangbin; Wu, Yifan; Ma, Xiaowei; Shen, Jianzhong; Zhu, Kui
Abstract: Antibiotic treatment failure against life-threatening bacterial pathogens is typically caused by the rapid emergence and dissemination of antibiotic resistance. The current lack of antibiotic discovery and development urgently calls for new strategies to combat multidrug-resistant (MDR) bacteria, especially those that survive in host cells. Functional nanoparticles are promising intracellular drug delivery systems whose advantages include their high biocompatibility and tunable surface modifications. Inspired by the fact that the rigidity of nanoparticles potentiates their cellular uptake, rigidity-functionalized nanoparticles (RFNs) coated with bacteria-responsive phospholipids were fabricated to boost endocytosis, resulting in the increased accumulation of intracellular antibiotics. Precise delivery and high antibacterial efficacy were demonstrated by the clearing of 99% of MDR bacteria in 4 h using methicillin-resistant Staphylococcus aureus (MRSA) and pathogenic Bacillus cereus as models. In addition, the subcellular distribution of the RFNs was modulated by altering the phospholipid composition on the surface, thereby adjusting the electrostatic effects and reprograming the intracellular behavior of the RFNs by causing them to accurately target lysosomes. Finally, the RFNs showed high efficacy against MRSA-associated infections in animal models of wound healing and bacteremia. These findings provide a controllable rigidity-regulated delivery platform with responsive properties for precisely reprograming the accumulation of cytosolic antibiotics, shedding light on precision antimicrobial therapeutics against intracellular bacterial pathogens in the future.